Conception of national bibliography in modern science of bibliography - Чяпите, Юлия (Knygotyra, 1987)
The modern scientific classification of bibliography has to include the concept of “national bibliography”. Thus: 1) bibliographic classifications of this world-wide and specific for all countries phenomenon must be originated and 2) it has to be decide whether the term “national bibliography” is suitable to all countries.The inclusion of the notion “national bibliography” into the bibliographic classification depends upon the concept of national bibliography. According to one of the concepts the term “national bibliography” is not suitable when the bibliographical control of the press of a multinational country (including the USSR) is taken into consideration, The term “national bibliography” should be given up and instead of it a common notion, suitable for all countries should be found in the bibliographic classification. But it would disagree with the international use of the conception. The other conception of “national bibliography” suggests to use the term “national bibliography” in all countries conditionally, including multinational countries too. In this case the term “national bibliography” as well as the term “catalogue bibliography” might be used in the bibliographic classification as a branch of general bibliography.